Isolation of Silica-Lignin Composites from Rice Husk and Their Adsorption to Cr(VI) - Yati B. Yuliyati; Seli Listiani; Solihudin Solihudin; Atiek Rostika Noviyanti (ALCHEMY Jurnal Penelitian Kimia, 2018)
Rice husk is the most abundant agricultural waste in Indonesia. It can be used as a precursor for multifunctional materials such as silica-lignin composite for adsorbents. Silica-lignin can reduce heavy metal content in an industrial waste, such as the content of Cr(VI). This study aims to isolate and characterize silica-lignin composite, and determines the isotherm type of silica-lignin for hexavalent chromium adsorption. The isolation from rice husk used an alkali extraction method. Confirmation of typical functional groups in the silica-lignin composite was characterized by FTIR, while the morphology was characterized by SEM, respectively. The results reveal that the silica-lignin isolation was successfully performed.  FTIR spectra indicate a typical wavenumber of the silica-lignin.  The SEM image of the composite showed homogeneous morphology. The silica-lignin adsorption process on hexavalent chromium followed a Brunauer–Emmett–Teller (BET) isotherm type indicated by multilayer adsorption with a surface area of 948.8421 mg. g-1.